ANALISIS STRATEGI PEMASARAN INDOVISION PADA PT MNC SKY VISION JAKARTA BARAT - Ophie Ophie; Euis Komalawati; R Parianom (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to determine the right and competitive marketing strategy by first identifying and assessing the company's internal and external factors that affect the company. This is done using the SWOT Analysis method and the 7P Strategy. This research was conducted using survey methods (interviews and observations) on Indovision marketing, Indovision sales, Indovision customers, marketing strategy academics. The results are then analyzed which is used to evaluate the opportunities and threats in the business environment as well as the internal strengths and weaknesses of the company. Companies can use the company's previous strategy by improving some of the company's weaknesses and avoiding or defending against company threats by creating a more competitive strategy.